1990
DOI: 10.2224/sbp.1990.18.2.309
|View full text |Cite
|
Sign up to set email alerts
|

Treating Factor Interpretations as Hypotheses

Abstract: Factor analysis is used extensively in the construction of psychometric scales. It may appear to be a mathematically precise and objective technique, but it involves many subjective choices and its results require subjective interpretation. Factor interpretations are hypotheses that should be tested, yet often are accepted simply on the basis of post hoc expert judgment. Untested judgments about the meaning of factors sometimes result in mislabeling of published scales and misinterpretation of research findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A survey of the items that loaded on Factor 1 suggested that this factor encompasses the beliefs that being uncertain impairs behavior and reflects badly on an individual’s character; accordingly, this factor was labeled “Uncertainty Has Negative Behavioral and Self-Referent Implications.” The second set of items reflected the belief that the future should be predictable and that unpredictability is unfair and therefore distressing; accordingly, Factor 2 was labeled “Uncertainty Is Unfair and Spoils Everything.” Both factor labels therefore showed face validity for the items they comprise. Nonetheless, Tracy (1990) has recommended that additional methods be employed to assess the validity of factor labels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A survey of the items that loaded on Factor 1 suggested that this factor encompasses the beliefs that being uncertain impairs behavior and reflects badly on an individual’s character; accordingly, this factor was labeled “Uncertainty Has Negative Behavioral and Self-Referent Implications.” The second set of items reflected the belief that the future should be predictable and that unpredictability is unfair and therefore distressing; accordingly, Factor 2 was labeled “Uncertainty Is Unfair and Spoils Everything.” Both factor labels therefore showed face validity for the items they comprise. Nonetheless, Tracy (1990) has recommended that additional methods be employed to assess the validity of factor labels.…”
Section: Discussionmentioning
confidence: 99%
“…Both factor labels therefore showed face validity for the items they comprise. Nonetheless, Tracy (1990) has recommended that additional methods be employed to assess the validity of factor labels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, it avoids the subjec-tivity in factor loadings interpretation (Fairweather, 2001;P. Jordan & Spiess, 2019;Tracy, 1990;Wrigley, 1958). Our approach overcomes this aspect by focusing on items instead of latent factors.…”
Section: Discussionmentioning
confidence: 99%